2005
DOI: 10.1359/jbmr.050326
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Bone Morphology and Bone Quality in Male Tibias: Implications for Stress Fracture Risk

Abstract: Biomechanical properties were assessed from the tibias of 17 adult males 17-46 years of age. Tissue-level mechanical properties varied with bone size. Narrower tibias were comprised of tissue that was more brittle and more prone to accumulating damage compared with tissue from wider tibias.Introduction: A better understanding of the factors contributing to stress fractures is needed to identify new prevention strategies that will reduce fracture incidence. Having a narrow (i.e., more slender) tibia relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 59 publications
(124 reference statements)
5
103
0
2
Order By: Relevance
“…Bone tissue is brittle in narrower tibia, supporting the notion that increased Ct.Dn is a compensatory mechanism for a structurally weaker bone, as shown in male cadaveric specimens [50], in vivo in women [37], and in stress fracture cases [51,52]. In support of these previous findings, volumetric Ct.Dn was inversely related to periosteal (and endosteal) perimeter at Baseline, indicating that those with lower crosssectional area had higher Ct.Dn.…”
Section: Discussionsupporting
confidence: 76%
“…Bone tissue is brittle in narrower tibia, supporting the notion that increased Ct.Dn is a compensatory mechanism for a structurally weaker bone, as shown in male cadaveric specimens [50], in vivo in women [37], and in stress fracture cases [51,52]. In support of these previous findings, volumetric Ct.Dn was inversely related to periosteal (and endosteal) perimeter at Baseline, indicating that those with lower crosssectional area had higher Ct.Dn.…”
Section: Discussionsupporting
confidence: 76%
“…A recent study by Tommasini et al 45 showed that narrower tibia may be at higher risk of stress fractures not only due to higher tissue stresses caused by smaller size of the bone but also because of the higher susceptibility of its tissue properties for damage accumulation than wider tibia. Their data demonstrated that narrower tibiae were more brittle and more prone to damage accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is variations in tissue material properties. Variations in tissue material properties (often associated with degree of mineralization) have been shown to influence trabecular bone biomechanics [18,[32][33][34][35] and have been noted in humans and rodents [36].…”
Section: What Do We Know About Trabecular Bone Quality?mentioning
confidence: 99%